Understanding Interleukin 33 and Its Roles in Eosinophil Development - Johnston, Laura K.; Bryce, Paul J. (Frontiers in Medicine, 2017)
Over the last decade, significant interest in the contribution of three “epithelial-derived cytokines,” such as thymic stromal lymphopoietin, interleukin 25, and interleukin 33 (IL-33), has developed. These cytokines have been strongly linked to the early events that occur during allergen exposures and how they contribute to the subsequent type 2 immune response. Of these three cytokines, IL-33 has proven particularly interesting because of the strong associations found between both it and its receptor, ST2, in several genome-wide association studies of allergic diseases. Further work has demonstrated clear mechanisms through which this cytokine might orchestrate allergic inflammation, including activation of several key effector cells that possess high ST2 levels, including mast cells, basophils, innate lymphoid cells, and eosinophils. Despite this, controversies surrounding IL-33 seem to suggest the biology of this cytokine might not be as simple as current dogmas suggest including: the relevant cellular sources of IL-33, with significant evidence for inducible expression in some hematopoietic cells; the mechanistic contributions of nuclear localization vs secretion; secretion and processing mechanisms; and the biological consequences of IL-33 exposure on different cell types. In this review, we will address the evidence for IL-33 and ST2 regulation over eosinophils and how this may contribute to allergic diseases. In particular, we focus on the accumulating evidence for a role of IL-33 in regulating hematopoiesis and how this relates to eosinophils as well as how this may provide new concepts for how the progression of allergy is regulated.